Evaluation of the videoscopic inguinal lymphadenectomy in melanoma patients. Issue 9 (September 2019) - Vrielink, Otis M.; Faut, Marloes; Deckers, Eric A.; van Leeuwen, Barbara L.; Been, Lucas B.
Abstract: Introduction: A completion or therapeutic inguinal lymph node dissection is a procedure accompanied with a high rate of postoperative complications. A novel, minimally invasive alternative has been developed; the videoscopic inguinal lymphadenectomy. The aim of this study is to present our first experience with the videoscopic inguinal lymphadenectomy among melanoma patients with inguinal metastases. Methods: Melanoma patients with a histologically confirmed inguinal metastases who underwent a videoscopic inguinal lymphadenectomy between November 2015 and January 2018 were included. Outcome measures were operation time, nodal yield, and postoperative complications. Furthermore, lymphedema measurements were performed both subjectively and objectively. Results: A total of 20 patients (3 males and 17 females) underwent a videoscopic inguinal lymphadenectomy. In 75% of patients the procedure was combined with an open iliac lymphadenectomy. Median operation time of the videoscopic procedure was 110 min (range, 79–165). There were no perioperative complications or conversions. In 12 patients (60%) there was ≥1 postoperative complication. The most frequent complications were seroma and wound infection. All complications were treated conservatively without the need for a surgical re-intervention. The median nodal yield of the videoscopic procedure was 9 (range, 1–19). Lymphedema was present in nine patients (45%) after three months of follow-up. Conclusion: Our initial results show that the videoscopic inguinal lymphadenectomy is an attractive alternative to the conventional open technique. The number of complications is comparable with the complication rate reported for the conventional open procedure, but they are less severe and there is no need for a surgical re-intervention.